Food safety, security and sustainability : Festschrift in honour to the work of Prof Dr H.C. Huub Lelieveld - Bogueva, Diana,; Rijn, Isabella van, (European Institute for Food Law series ;, 2025)
This Festschrift honors the remarkable career of Prof. Dr.h.c. Huub Lelieveld, celebrating his 80th birthday and the 20th anniversary of the Global Harmonization Initiative (GHI). Spanning a distinguished career across industry, academia, and public service, Huub's dedication to excellence, innovation, and ethics has profoundly impacted all those who have worked with him, from colleagues at Unilever to members of the GHI. This compilation of research papers, contributed by friends and colleagues who have collaborated with Huub, explores diverse and significant topics close to his heart. These include the realization of food culture, nutrition, food safety, religious food regulations during times of conflict, food fortification, novel food technologies like irradiation, improving religious slaughter practices, safe cassava consumption, and sustainable food futures and environmental responsibility and planetary health. Each article serves as a tribute to his vision and legacy, highlighting his lasting influence on global food science and public health.